EPCO-01. MOLECULAR PROFILING OF SPINAL CORD EPENDYMOMA. (12th November 2021) - Yamazawa, Erika; Tanaka, Shota; Nagae, Genta; Umeda, Takayoshi; Hana, Taijun; Kim, Phyo; Higuchi, Fumi; Takami, Toshihiro; Nakanishi, Yuta; Takai, Keisuke; Komori, Takashi; Takami, Hirokazu; et al.
Abstract: BACKGROUND: Ependymomas are currently classified into 9 subgroups by DNA methylation profiles. Although spinal cord ependymoma (SP-EPN) is distinct from other tumors, diversity within SP-EPN is still unclear. Here, we used transcriptomic and epigenomic profiles to investigate the diversity among Japanese SP-EPN cases. MATERIALS AND METHODS: We analyzed 57 SP-EPN patients (32 males and 25 females, aged from 18 to 78 years, median: 52), including two cases of neurofibromatosis type 2, five cases of grade 3 (WHO grade). We obtained transcriptome (RNA-seq) and DNA methylation (Infinium Methylation EPIC array) data from fresh frozen specimens of SP-EPN resected at the University of Tokyo Hospital and our collaborative groups. RESULTS: Three cases had a previous intracranial ependymoma operation. Hierarchical clustering of the DNA methylation data showed that these three cases of intracranial origin as a different cluster from spinal origin. The 45 grade 2 spinal ependymoma showed a relatively homogenous methylation pattern. However, the methylation status of HOX gene cluster regions is compatible with the segment of origin, which reflects the cells of origins are derived after the determination of segment identity. RNA sequencing of 57 cases revealed two subgroups within grade 2. Gene ontology analysis of differentially expressed genes suggested the difference in metabolic state such as rRNA translation and mitochondrial respiration between the two expression subgroups. CONCLUSION: Epigenetic analysis indicated the accurate body segment origin of SP-EPN. We observed that metabolic states could divide grade 2 spinal cord ependymoma into 2 subgroups and will present the relationship to clinicopathological information.